Development of a Greener Monkey Repellent: Fermentation-Derived Biological Communication Method for Wildlife Management - Teo, Chee Loong (Journal of Emerging Technologies and Industrial Applications, 2024)
Wildlife management is crucial for maintaining biodiversity and mitigating human-wildlife conflicts, which can result in significant agricultural losses and safety risks. Traditional repellents often rely on harsh chemicals or physical barriers even electrical fencing that may pose environmental hazards and be only partially effective. This highlights the need for innovative solutions that are both effective and environmentally friendly. This study introduces a novel bio-repellent developed through biological communication methods, specifically targeting the mitigation of monkey intrusions in agricultural zones. The repellent utilizes fermentation-derived scents designed to communicate deterrent signals to monkeys without harming them and the environment. The repellent was developed using a natural fermentation process that produces olfactory compounds known to be aversive to monkeys. Field testing (Kota Tinggi, Johor and Muar, Johor) was conducted in high-conflict agricultural areas to assess the repellent's effectiveness and ecological impact. Efficacy was measured by the decrease in wildlife intrusions, and environmental impact assessments were performed to ensure the repellent's safety. The bio-repellent demonstrated a significant reduction in monkey intrusions, with efficacy rates nearly 100% in treated areas. Environmental impact assessments indicated no adverse effects on the local fauna and flora, supporting the repellent's safety and sustainability. The development of this monkey bio-repellent represents a significant advancement in wildlife management practices. It offers a viable solution for reducing human-wildlife conflicts through a non-invasive, biologically-based approach. The implications of these findings are promising for broader applications in wildlife management globally, potentially addressing various types of human-wildlife conflicts with similar biotechnological strategies.